2021
DOI: 10.1177/2050313x211029154
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical treatment for periodontitis and peri-implantitis: longitudinal clinical and bacteriological findings—A case report with a 7-year follow-up evaluation

Abstract: The aim of this report is to show that periodontitis and peri-implantitis with horizontal bone resorption in a 68-year-old male patient were successfully treated by non-surgical treatment. Scaling with an ultrasonic device was performed for moderate periodontitis around the mandibular left first premolar and moderate peri-implantitis around the maxillary right molar implants. Root planing with a metal curette was performed for the periodontal site, and debridement with a plastic curette was performed for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Moreover, abundance alteration could happen to part of the 14 genera screened after the treatment of peri‐implant disease. The relative abundance of Tannerella and Porphyromonas decreased after nonsurgical treatment for peri‐implantitis, whereas the relative abundance of Rothia increased (Shiba et al, 2021). A study found Porphyromonas and Treponema could be influenced by peri‐implantitis treatment (Nie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, abundance alteration could happen to part of the 14 genera screened after the treatment of peri‐implant disease. The relative abundance of Tannerella and Porphyromonas decreased after nonsurgical treatment for peri‐implantitis, whereas the relative abundance of Rothia increased (Shiba et al, 2021). A study found Porphyromonas and Treponema could be influenced by peri‐implantitis treatment (Nie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the V4 region should be included in the primer design since the V4 region was the best sub-region for phylogenetic resolution among other 16S rRNA gene variable regions (Yang et al, 2016). In modern research for bacterial composition in the oral cavity, many reports using the V3-V4 region have been performed, and good results have been reported (Maruyama et al, 2014;Komatsu et al, 2020;Shiba et al, 2021;Shimogishi et al, 2021). In contrast, many studies have shown effective results using ancient microbiome through the amplicon sequencing of the V4 region (Santiago-Rodriguez et al, 2017;Santiago-Rodriguez et al, 2019) because ancient DNA is known to be highly fragmented (Sawyer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The libraries were then sequenced on the MiSeq platform (Illumina, CA, USA) to obtain 2 × 300 bp paired-end reads. 17,18 The read data were submitted to the DNA Data Bank of Japan (http://www.ddbj.nig. ac.jp/) under accession number DRA012487.…”
Section: Results Of Bacteriological Examinationmentioning
confidence: 99%
“…High-throughput sequencing technology is ideal for the comprehensive evaluation of changes in bacterial composition in polymicrobial diseases prior to and post-treatment. 18 Here, we report two cases that had an apically positioned flap (APF) combined with IP and erbiumdoped yttrium aluminum garnet (Er:YAG) laser irradiation, before and after implantoplasty (IP), for peri-implantitis treatment; and with FGG to increase the KM and oral vestibule. The clinical and bacteriological effects of the treatments were evaluated longitudinally via high-throughput sequencing.…”
mentioning
confidence: 99%